Combined TLR7/8 and TLR9 ligands potentiate the activity of a Schistosoma japonicum DNA vaccine. - Xuefeng Wang; Liyang Dong; Hongchang Ni; Sha Zhou; Zhipeng Xu; Jason Shih Hoellwarth; Xiaojun Chen; Rongbo Zhang; Qiaoyun Chen; Feng Liu; Jun Wang; Chuan Su (Public Library of Science (PLoS), 2013)
BACKGROUND: Toll-like receptor (TLR) ligands have been explored as vaccine adjuvants for tumor and virus immunotherapy, but few TLR ligands affecting schistosoma vaccines have been characterized. Previously, we developed a partially protective DNA vaccine encoding the 26-kDa glutathione S-transferase of Schistosoma japonicum (pVAX1-Sj26GST). METHODOLOGY/PRINCIPAL FINDINGS: In this study, we evaluated a TLR7/8 ligand (R848) and a TLR9 ligand (CpG oligodeoxynucleotides, or CpG) as adjuvants for pVAX1-Sj26GST and assessed their effects on the immune system and protection against S. japonicum. We show that combining CpG and R848 with pVAX1-Sj26GST immunization significantly increases splenocyte proliferation and IgG and IgG2a levels, decreases CD4(+)CD25(+)Foxp3(+) regulatory T cells (Treg) frequency in vivo, and enhances protection against S. japonicum. CpG and R848 inhibited Treg-mediated immunosuppression, upregulated the production of interferon (IFN)-γ, tumor necrosis factor (TNF)-α, interleukin (IL)-4, IL-10, IL-2, and IL-6, and decreased Foxp3 expression in vitro, which may contribute to prevent Treg suppression and conversion during vaccination and allow expansion of antigen-specific T cells against pathogens. CONCLUSIONS: Our data shows that selective TLR ligands can increase the protective efficacy of DNA vaccines against schistosomiasis, potentially through combined antagonism of Treg-mediated immunosuppression and conversion.